Pharmacokinetic equivalence of CT‐P17 to high‐concentration (100 mg/ml) reference adalimumab: A randomized phase I study in healthy subjects. Issue 4 (2nd March 2021) - Yu, Kyung‐Sang; Jang, In‐Jin; Lim, Hyeong‐Seok; Hong, Jang Hee; Kim, Min‐Gul; Park, Min Kyu; Cho, Doo‐Yeoun; Park, Min Soo; Chung, Jae Yong; Ghim, Jong‐Lyul; Lee, SeungHwan; Yoon, Seok Kyu; et al.
Abstract: This study aimed to demonstrate pharmacokinetic (PK) equivalence of a single dose of the proposed adalimumab biosimilar CT‐P17 to United States‐licensed adalimumab (US‐adalimumab) and European Union‐approved adalimumab (EU‐adalimumab). This double‐blind, parallel‐group, phase I trial (clinicaltrials.gov NCT03970824) was conducted at 10 hospitals (Republic of Korea), in which healthy subjects (1:1:1) were randomized to receive a single 40 mg (100 mg/ml) subcutaneous injection of CT‐P17, US‐adalimumab, or EU‐adalimumab. Primary end points were PK equivalence in terms of: area under the concentration–time curve from time zero to infinity (AUC0–inf ); AUC from time zero to the last quantifiable concentration (AUC0–last ); and maximum serum concentration (Cmax ). PK equivalence was concluded if 90% confidence intervals (CIs) for percent ratios of geometric least squares means (GLSMs) for pairwise comparisons were within the equivalence margin of 80–125%. Additional PK end points, safety, and immunogenicity were evaluated. Of the 312 subjects who were randomized (103 CT‐P17; 103 US‐adalimumab; 106 EU‐adalimumab), 308 subjects received study drug. AUC0–inf, AUC0–last, and Cmax were equivalent among CT‐P17, US‐adalimumab, and EU‐adalimumab, because 90% CIs for the ratios of GLSMs were within the 80–125% equivalence margin for each pairwise comparison. Secondary PK end points, safety, and immunogenicity were similar between treatment groups. In conclusion, PK equivalence for single‐dose administration of CT‐P17, EU‐adalimumab, and US‐adalimumab was demonstrated in healthy adults. Safety and immunogenicity profiles were comparable between treatment groups and consistent with previous reports for adalimumab biosimilars.